Goal-Oriented Respiratory Management for Critically Ill Patients with Acute Respiratory Distress Syndrome - Carmen Sílvia Valente Barbas; Gustavo Faissol Janot Matos; Marcelo Britto Passos Amato; Carlos Roberto Ribeiro Carvalho (Critical Care Research and Practice)
This paper, based on relevant literature articles and the authors' clinical experience, presents a goal-oriented respiratory management for critically ill patients with acute respiratory distress syndrome (ARDS) that can help improve clinicians' ability to care for these patients. Early recognition of ARDS modified risk factors and avoidance of aggravating factors during hospital stay such as nonprotective mechanical ventilation, multiple blood products transfusions, positive fluid balance, ventilator-associated pneumonia, and gastric aspiration can help decrease its incidence. An early extensive clinical, laboratory, and imaging evaluation of “at risk patients” allows a correct diagnosis of ARDS, assessment of comorbidities, and calculation of prognostic indices, so that a careful treatment can be planned. Rapid administration of antibiotics and resuscitative measures in case of sepsis and septic shock associated with protective ventilatory strategies and early short-term paralysis associated with differential ventilatory techniques (recruitment maneuvers with adequate positive end-expiratory pressure titration, prone position, and new extracorporeal membrane oxygenation techniques) in severe ARDS can help improve its prognosis. Revaluation of ARDS patients on the third day of evolution (Sequential Organ Failure Assessment (SOFA), biomarkers and response to infection therapy) allows changes in the initial treatment plans and can help decrease ARDS mortality.